Stabilized reductive iron-sulfur-based slurry as well as preparation method and application thereof
By using organic matter and divalent iron ions complexed and coagulant in iron-sulfur-based materials to enhance oxidation resistance, forming a stable iron-sulfur-based slurry, solving the problems of complex preparation, unstable storage and low removal ability of existing materials, and achieving efficient and stable water-body heavy metal removal effect.
Patent Information
- Application Number
- CN202411851026.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing iron-sulfur-based materials have disadvantages in terms of complex preparation process, unstable storage, low concentration of iron-sulfur element and difficulty in achieving large-scale production. NanoFeS is very easy to agglomerate and be oxidized, resulting in a decrease in its ability to reduce pollutants.
The organic matter-coagulant-ferrous sulfide nanoparticle suspension is used to complex the organic matter with divalent iron ions to reduce oxidation and agglomeration, and enhance oxidation resistance through coagulant to form a stable iron-sulfur-based slurry.
It improves the dispersion, stability and reactivity of iron-sulfur-based materials, extends storage time, enhances the removal ability of heavy metals in water, and the removal rate reaches more than 99.86%, and avoids secondary pollution and yellowing of reaction products.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a water treatment slurry and a preparation method and application thereof, and in particular to a stabilized reducing iron-sulfur based slurry and a preparation method and application thereof. Background Art
[0002] Iron-sulfur-based materials have attracted extensive attention due to their excellent reducibility and wide application potential. Such materials have important application value in water treatment, heavy metal removal and environmental remediation. Especially in the removal of heavy metals in water bodies, iron-sulfur-based materials can effectively remove heavy metal ions in water, such as chromium, cadmium, lead, etc., through chemical reduction reactions, reducing their toxicity and bioavailability.
[0003] Traditional iron-sulfur-based materials usually have the disadvantages of complex preparation process, unstable storage, low iron and sulfur concentration, and difficulty in large-scale production. Based on the problem of easy oxidation and unstable aggregation of micro-nano particles, existing studies mostly use stabilizers (such as silicates, organic complexes or organic polymers, etc.) and dilute solution preparation methods to prepare colloids or emulsions, but the iron and sulfur content of the obtained iron-sulfur-based materials is low. In the actual application process, there are problems such as large dosage, easy loss, poor durability, and easy rebound of treatment effect, which seriously restrict the application of iron-sulfur-based materials. Compared with other iron-sulfur-based materials, ferrous sulfide (FeS), as a heavy metal stabilizer, contains two reducing substances, ferrous ions and sulfur ions, has good reducibility, and has many unique advantages in the field of water treatment. However, FeS nanoparticles are very easy to agglomerate and oxidize during actual application, which leads to a decrease in their ability to reduce and remove pollutants. Therefore, how to modify nano-FeS, enhance the dispersibility, stability and reactivity of nano-FeS, and improve the stability of its production and storage and transportation process has become a current research hotspot. The current development trend of FeS modification research is to load, embed or stabilize FeS nanoparticles to improve their antioxidant, reducibility and stability.
[0004] The existing research on the modification of nano-FeS generally includes two methods: coating stabilizers and loading support materials. Adding stabilizers can form a negatively charged film on the surface of nanoparticles during the synthesis of FeS, providing strong spatial resistance and electrostatic repulsion, and effectively controlling the FeS particle size, such as: using sodium carboxymethyl cellulose (CMC), sericin, ascorbic acid, and acrylic resin to coat brown sugar-modified nano-iron materials. The particle size can be adjusted by mineral, carbon-based and other loading materials, and the particle permeability can be enhanced. At the same time, nano-FeS can be effectively dispersed and the occurrence of agglomeration can be reduced, such as: biochar selected in Chinese patents CN108996710A and CN106966456A, magnesium-based selected in Chinese patents CN108620047A, and Al2O3 selected in (Li Ning, et al., 2013) as loading materials. The above research results on modified FeS materials all have problems such as low iron and sulfur content, easy oxidation, agglomeration and sedimentation, and low decontamination efficiency, and lack research on storage stability.
[0005] Currently, the following problems still exist in the practical application of modified FeS: (1) The content of effective components in the dispersed ferrous sulfide colloid is low, which makes it easy to lose and dilute during practical application; (2) The introduced stabilizer or loading material may cause secondary pollution to the environment, or the stability of the product after the reaction is poor, which is prone to yellowing and pollutant re-release; (3) Most nano-FeS materials have problems such as difficulty in large-scale preparation, storage, and short shelf life, which has become a bottleneck problem for the large-scale application of FeS. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a stabilized reducing iron-sulfur based slurry which can reduce the deactivation of FeS oxidation agglomeration and increase the content of reducing iron-sulfur and is easy to store;
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned stabilized reducing iron-sulfur based slurry;
[0008] The third object of the present invention is to provide the application of the above-mentioned stabilized reducing iron-sulfur based slurry.
[0009] Technical solution: The stabilized reducing iron-sulfur based slurry described in the present invention is an organic matter-coagulant-ferrous sulfide nanoparticle suspension; the slurry comprises the following components in terms of mass percentage concentration: organic matter: 0.5-5%, coagulant: 1-10%, and ferrous sulfide nanoparticles: the balance.
[0010] Wherein, the organic matter is at least one of humic acid, disodium salt of ethylenediaminetetraacetic acid, aminotrimethylenephosphonate, ethylenediaminetetramethylenephosphonate or hydroxymethylenephosphonate; the coagulant is at least one of polyferric sulfate, polyaluminum chloride, polyacrylamide or dicyandiamide resin organic coagulant; the particle size of the ferrous sulfide nanoparticles is 500-1000nm.
[0011] The method for preparing the above-mentioned stabilized reducing iron-sulfur based slurry comprises the following steps:
[0012] (1) mixing the organic matter solution with the ferrous sulfate solution and stirring to allow the ferrous ions to fully complex with the organic matter;
[0013] (2) mixing the coagulant solution with the solution obtained in step (1), stirring, and encapsulating the complex of ferrous ions and organic matter therein;
[0014] (3) slowly adding sodium sulfide solution to the mixed solution obtained in step (2), stirring to form nano-ferrous sulfide particles in the mixed solution, and then centrifuging and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension.
[0015] Wherein, the volume ratio of the organic solution, coagulant, ferrous sulfate solution and sodium sulfide solution is 5:5:2:1-3:3:2:1.
[0016] Wherein, in step (1), the mass percentage concentration of the added organic solution is 0.5-5%, and the mass percentage concentration of the added ferrous sulfate solution is 5-15 mol / L.
[0017] Wherein, in step (1), the stirring speed is 200-500 rpm and the stirring time is 5-10 min.
[0018] Wherein, in step (2), the mass percentage concentration of the coagulant solution is 1-10%.
[0019] Wherein, in step (2), the stirring speed is 200-500 rpm and the time is 5-10 min.
[0020] The ferrous sulfide content in the organic matter-coagulant-ferrous sulfide nanoparticle suspension obtained in step (3) is not higher than 80 g / L and not lower than 40 g / L.
[0021] Wherein, in step (3), the molar concentration of the added sodium sulfide solution is 5-20 mol / L.
[0022] Wherein, in step (3), after the sodium sulfide solution is added dropwise, the stirring speed is 200-500 rpm; the time is 5-10 min; and the centrifugal speed is 3000-6000 rpm.
[0023] The above-mentioned stabilized reducing iron-sulfur based slurry is used for removing heavy metals from water bodies.
[0024] The application method is as follows: adding the prepared heavy metal removal material to water containing heavy metal chromium so that the volume ratio of the two is about 200:1-100:1, stirring at a speed of 200-500rpm for 10-30min, and removing the chromium from the water through static sedimentation and solid-liquid separation; wherein the removal rate of chromium in the water reaches more than 99.86%.
[0025] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0026] (1) The iron-sulfur-based slurry of the present invention reduces the oxidation of divalent iron by complexing the organic matter with the divalent iron ions, so that the divalent iron is dispersed, which is beneficial to the growth and dispersion of FeS. At the same time, the presence of organic matter changes the amount of charge on the surface of the nano-FeS particles, enhances the spatial resistance and electrostatic repulsion in the suspension system, thereby improving the dispersibility of FeS and preventing the agglomeration of FeS during its formation. In addition, by combining the organic matter with the flocculant, most of the divalent iron forms FeS particles through in-situ reaction and is wrapped by macromolecules, thereby improving the oxidation resistance of the FeS particles. (2) The iron-sulfur-based slurry of the present invention can be stored for a long time, and can be stored for more than one month at room temperature. (1) The iron-sulfur slurry of the present invention has the following characteristics: (1) It can meet the requirements of transportation and storage in practical applications; (2) Compared with existing iron-sulfur materials, the iron-sulfur slurry of the present invention has the characteristics of good environmental adaptability and environmental compatibility; (3) The iron-sulfur slurry of the present invention has the characteristics of good environmental adaptability and environmental compatibility; (4) The preparation method of the iron-sulfur slurry of the present invention is simple, the raw materials are easily available, the process is short, no complicated synthesis equipment and harsh synthesis conditions are required, and the operation is convenient; (5) When the iron-sulfur slurry of the present invention is used to treat heavy metal-contaminated water, it is easy to disperse quickly in water, and the reaction speed is fast, and the chromium removal rate in water is more than 99.86%; (6) When treating heavy metal-contaminated water, the process is easy to control, the reaction products are stable, and no yellowing or re-release of pollutants occurs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The actual picture of the pure ferrous sulfide nanoparticle suspension prepared in Comparative Example 1 and the stabilized reducing iron-sulfur based slurry prepared in Examples 1-3 after being sealed and stored at room temperature for 24 hours;
[0028] Figure 2 This is a physical picture of the stabilized reducing iron-sulfur based slurry prepared in Example 3 after being sealed and stored at room temperature for 30 days;
[0029] Figure 3 The scanning electron microscope images are of the FeS repair agent prepared in Comparative Example 1 and the stabilized reducing iron-sulfur based slurry prepared in Example 1;
[0030] Figure 4 This is a graph showing the change in removal rate when the stabilized reducing iron-sulfur based slurry prepared in Example 1 is used to remove a solution containing hexavalent chromium at a concentration of 40 mg / L. DETAILED DESCRIPTION
[0031] The present invention is described in further detail below.
[0032] Example 1
[0033] A stabilized reducing iron-sulfur based slurry is an organic matter-coagulant-ferrous sulfide nanoparticle suspension; the slurry comprises the following components by mass percentage concentration: organic matter: 0.5%, coagulant: 1%, ferrous sulfide nanoparticles: 98.5%. The organic matter is humic acid (HA) and the coagulant is polyaluminium chloride (PAC); the preparation method of the slurry comprises the following steps:
[0034] (1) Dissolving humic acid, polyaluminium chloride, ferrous sulfate and sodium sulfide in water respectively to prepare a 0.5% by weight humic acid solution, a 1% by weight polyaluminium chloride solution, a 5 mol / L ferrous sulfate solution and a 10 mol / L sodium sulfide solution; mixing the humic acid solution and the ferrous sulfate solution at room temperature and in the absence of oxygen, and stirring at 500 rpm for 6 min to allow the ferrous ions to fully complex with the humic acid;
[0035] (2) mixing the polyaluminium chloride solution with the solution obtained in step (1), stirring at 400 rpm for 10 min to encapsulate the complex of ferrous ions and humic acid;
[0036] (3) slowly adding sodium sulfide solution to the solution obtained in step (2), stirring at 500 rpm for 30 min, centrifuging the mixed solution at 4000 rpm and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension, i.e., a stabilized reducing iron-sulfur based slurry;
[0037] Among them, the volume ratio of humic acid solution: polyaluminium chloride solution: ferrous sulfate solution: sodium sulfide solution is 5:5:2:1.
[0038] The stabilized reducing iron-sulfur based slurry prepared in Example 1 is applied to treat water containing heavy metal chromium, and the specific steps are as follows:
[0039] The stabilized reducing iron-sulfur based slurry prepared in Example 1 was added to the water containing heavy metal chromium so that the volume ratio of the two was about 100:1, and the mixture was stirred at 300 rpm for 20 min to obtain the repaired water body; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 40 mg / L.
[0040] The results showed that after 20 minutes, the removal rate of active chromium in water was 98.31%. In the following 60 days, the total organic carbon content of the water was less than 4 mg / L, the water did not turn yellow, the total chromium content was less than 0.56 mg / L, and the total iron content was less than 0.38 mg / L.
[0041] Example 2
[0042] A stabilized reducing iron-sulfur based slurry is an organic matter-coagulant-ferrous sulfide nanoparticle suspension; the slurry comprises the following components by mass percentage: organic matter: 1%, coagulant: 2%, ferrous sulfide nanoparticles: 97%. The organic matter is ethylenediaminetetraacetic acid disodium salt (EDTA·Na2), and the coagulant is polyferric sulfate (PFS); the preparation method of the slurry comprises the following steps:
[0043] (1) dissolving ethylenediaminetetraacetic acid disodium salt, polyferric sulfate, ferrous sulfate, and sodium sulfide in water respectively to prepare a 1% by weight ethylenediaminetetraacetic acid disodium salt solution, a 2% by weight polyferric sulfate solution, an 8 mol / L ferrous sulfate solution, and a 12 mol / L sodium sulfide solution; mixing the ethylenediaminetetraacetic acid disodium salt solution and the ferrous sulfate solution at room temperature and in the absence of oxygen, and stirring at 300 rpm for 8 min to allow the ferrous ions to fully complex with the ethylenediaminetetraacetic acid disodium salt;
[0044] (2) mixing the polyferric sulfate solution with the solution obtained in step (1), stirring at 200 rpm for 5 min to encapsulate the complex of ferrous ions and disodium ethylenediaminetetraacetic acid;
[0045] (3) slowly adding sodium sulfide solution to the solution obtained in step (2), stirring at 400 rpm for 20 min, centrifuging the mixed solution at 5000 rpm and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension, i.e., a stabilized reducing iron-sulfur slurry;
[0046] Wherein, the volume ratio of ethylenediaminetetraacetic acid disodium salt solution: polyferric sulfate solution: ferrous sulfate solution: sodium sulfide solution is 5:5:2:1.
[0047] The stabilized reducing iron-sulfur based slurry prepared in Example 2 is applied to treat water containing heavy metal chromium, and the specific steps are as follows:
[0048] The prepared water body heavy metal removal material was added to water containing heavy metal chromium so that the volume ratio of the two was about 150:1, and the mixture was stirred at 300 rpm for 15 minutes to obtain the repaired water body; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 50 mg / L.
[0049] The results showed that after 15 minutes, the removal rate of active chromium in the water was 95.94%. In the following 60 days, the total organic carbon content of the water was less than 6 mg / L, the water did not turn yellow, the total chromium content was less than 2.03 mg / L, and the total iron content was less than 0.40 mg / L.
[0050] Example 3
[0051] A stabilized reducing iron-sulfur based slurry is an organic matter-coagulant-ferrous sulfide nanoparticle suspension; the slurry comprises the following components by mass percentage concentration: organic matter: 2%, coagulant: 4%, ferrous sulfide nanoparticles: 94%. The organic matter is hydroxymethylene phosphonate (HEDP) and the coagulant is polyacrylamide (PAM); the preparation method of the slurry comprises the following steps:
[0052] (1) Dissolving hydroxymethylene phosphonate, polyacrylamide, ferrous sulfate, and sodium sulfide in water respectively to prepare a 2% by weight hydroxymethylene phosphonate solution, a 4% by weight polyacrylamide solution, a 10 mol / L ferrous sulfate solution, and a 15 mol / L sodium sulfide solution; mixing the hydroxymethylene phosphonate solution and the ferrous sulfate solution at room temperature and in the absence of oxygen, and stirring at 200 rpm for 10 min to allow the ferrous ions to fully complex with the hydroxymethylene phosphonate;
[0053] (2) mixing the polyacrylamide solution with the solution obtained in step (1), and stirring at 500 rpm for 10 min to encapsulate the complex of ferrous ions and hydroxymethylenephosphonate;
[0054] (3) slowly adding sodium sulfide solution to the solution obtained in step (2), stirring at 500 rpm for 30 min, centrifuging the mixed solution at 4000 rpm and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension, i.e., a stabilized reducing iron-sulfur-based slurry; the above slurry is sealed and stored at room temperature for 1 month for later use.
[0055] The volume ratio of hydroxymethylene phosphonate solution: polyacrylamide solution: ferrous sulfate solution: sodium sulfide solution is 5:5:2:1.
[0056] The stabilized reducing iron-sulfur based slurry prepared in Example 3 is applied to treat water containing heavy metal chromium, and the specific steps are as follows:
[0057] The prepared stabilized reducing iron-sulfur-based slurry that had been allowed to stand at room temperature for 30 days was added to water containing heavy metal chromium so that the volume ratio of the two was about 150:1, and the slurry was stirred at 400 rpm for 15 minutes to obtain the repaired water body; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 60 mg / L.
[0058] The results showed that after 15 minutes, the removal rate of active chromium in the water was 98.73%. In the following 60 days, the total organic carbon content of the water was less than 7 mg / L, the water did not turn yellow, the total chromium content was less than 0.16 mg / L, and the total iron content was less than 0.45 mg / L.
[0059] The treatment effect of the iron-sulfur based slurry of each embodiment on chromium-containing water is shown in Table 1 below, and the water quality detection and evaluation of the iron-sulfur based slurry of each embodiment on chromium-containing water after two months (60 days) of treatment is shown in Table 2 below.
[0060] Table 1 Treatment effect of iron-sulfur based slurry on chromium-containing water in each embodiment
[0061] Cr concentration before addition (mg / L) Cr concentration after addition (mg / L) Removal rate (%) Example 1 40.00 0.56 99.86 Example 2 50.00 2.03 95.94 Example 3 60.00 0.76 98.73
[0062] Table 2 Evaluation of water quality of iron-sulfur based slurry in each embodiment after two months of treatment of chromium-containing water
[0063] Total organic carbon (mg / L) Total chromium (mg / L) Total Iron (mg / L) Example 1 <4 <0.56 <0.38 Example 2 <6 <2.03 <0.40 Example 3 <7 <0.76 <0.45
[0064] As shown in Table 2, the stabilized reducing iron-sulfur based slurry of the present invention has no secondary pollution to water bodies, and the reaction product is stable, and the total chromium and total iron contents are stable for a long time after repair.
[0065] Comparative Example 1
[0066] Based on Example 1, the difference from Example 1 is that humic acid and polyaluminium chloride are replaced with pure water, and the volume ratio of ferrous sulfate solution to sodium sulfide solution is 2:1, thereby obtaining an unmodified iron-sulfur based slurry.
[0067] The unmodified iron-sulfur based slurry is applied to treat water containing heavy metal chromium, and the specific steps are as follows:
[0068] The prepared new stabilized reducing iron-sulfur based slurry was added to water containing heavy metal chromium so that the volume ratio of the two was about 100:1, and the slurry was stirred at 300 rpm for 30 minutes to obtain the repaired water body; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 40 mg / L.
[0069] The results showed that after 30 minutes, the removal rate of active chromium in water was 62.31%. After the unmodified iron-sulfur based slurry was placed at room temperature for 3 days, it was completely oxidized and deteriorated.
[0070] like Figure 1 As shown, Figure 1 Figure a is the sedimentation status of the ferrous sulfide nanoparticle suspension prepared in Comparative Example 1 12 hours after preparation. Figure 1 b, c, and d are the sedimentation conditions of the stabilized reducing iron-sulfur based slurries prepared in Examples 1, 2, and 3, respectively, 24 hours after preparation. Figure 1As can be seen from Figure a, the treatment group of the ferrous sulfide particle suspension prepared without adding organic matter and coagulant in Comparative Example 1 had obvious sedimentation and stratification at 24 hours. However, the ferrous sulfide particle suspension prepared with organic matter had no obvious sedimentation at 24 hours. Figure 1 As shown in b, c, and d.
[0071] The scanning electron microscope image of the ferrous sulfide particles obtained in Comparative Example 1 is as follows: Figure 3 As shown in Figure a, it can be seen that the ferrous sulfide particles prepared without adding organic matter and coagulant have uneven particle sizes. Compared with the ferrous sulfide particles with an average particle size of 500±100nm prepared in Example 1, there is obvious agglomeration phenomenon, such as Figure 3 As shown in b.
[0072] The present invention investigates the stability of the iron-sulfur based slurry prepared in Examples 1-3, and finds that the iron-sulfur based slurry of the present invention can be kept stable for at least 1 month under normal temperature and closed conditions. Figure 2 The product picture of the iron-sulfur based slurry prepared in Example 1 after sealed storage at room temperature shows that the organic matter has the function of dispersing and stabilizing the ferrous sulfide suspension, and the coagulant has the function of improving the antioxidant property of ferrous sulfide. The ferrous sulfide prepared in Comparative Example 1 agglomerated within 24 hours. Figure 1 As shown in Figure a, it shows that the iron-sulfur based slurry of the present invention has a longer storage time than the common ferrous sulfide material.
[0073] The iron-sulfur-based slurry of the present invention is applied to the repair of water bodies polluted by heavy metals, and has the advantages of short repair period, good heavy metal removal effect, simple, mature and easy method. From the results of Examples 1-3, it can be seen that the stabilized reducing iron-sulfur-based slurry of the present invention can quickly remove chromium, with a removal rate of more than 95%, and can avoid secondary pollution, has potential promotion and application value, and is economical and reliable.
[0074] Comparative Example 2
[0075] On the basis of Example 1, the difference from Example 1 is that polyaluminium chloride is replaced with pure water; the volume ratio of humic acid: ferrous sulfate solution: sodium sulfide solution is 5:2:1, and an iron-sulfur based slurry is obtained.
[0076] The iron-sulfur-based slurry was applied to treat water containing heavy metal chromium. The specific steps were as follows: adding the prepared new stabilized reducing iron-sulfur-based slurry to water containing heavy metal chromium, making the volume ratio of the two about 100:1, stirring at 400 rpm for 50 minutes, and obtaining the repaired water; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 40 mg / L. The results showed that after 50 minutes, the removal rate of active chromium in the water was 71.16%.
[0077] Comparative Example 3
[0078] On the basis of Example 1, the difference from Example 1 is that humic acid is replaced with pure water; the volume ratio of polyaluminium chloride: ferrous sulfate solution: sodium sulfide solution is 5:2:1, and an iron-sulfur based slurry is obtained.
[0079] The iron-sulfur-based slurry was applied to treat water containing heavy metal chromium. The specific steps were as follows: adding the prepared new stabilized reducing iron-sulfur-based slurry to water containing heavy metal chromium, making the volume ratio of the two about 100:1, stirring at 400 rpm for 40 minutes, and obtaining the repaired water; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 45 mg / L. The results showed that after 50 minutes, the removal rate of active chromium in the water was 79.62%.
[0080] Comparative Example 4
[0081] On the basis of Example 2, different from Example 2, polyaluminum chloride is replaced with potassium aluminum alum (KAl(SO4)2·12H2O); the volume ratio of humic acid: potassium aluminum alum: ferrous sulfate solution: sodium sulfide solution is 4:4:2:1, and an iron-sulfur based slurry is obtained.
[0082] The iron-sulfur-based slurry was applied to treat water containing heavy metal chromium. The specific steps were as follows: adding the prepared new stabilized reducing iron-sulfur-based slurry to water containing heavy metal chromium, making the volume ratio of the two about 150:1, stirring at 300 rpm for 40 minutes, and obtaining the repaired water; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 50 mg / L. The results showed that after 40 minutes, the removal rate of active chromium in the water was 65.33%.
[0083] Comparative Example 5
[0084] On the basis of Example 2, the difference from Example 2 is that the volume ratio of ethylenediaminetetraacetic acid disodium salt solution: polyferric sulfate solution: ammonium ferrous sulfate solution: sodium sulfide solution is 15:15:2:1.
[0085] The iron-sulfur-based slurry was applied to treat water containing heavy metal chromium. The specific steps were as follows: adding the prepared new stabilized reducing iron-sulfur-based slurry to water containing heavy metal chromium, making the volume ratio of the two about 150:1, stirring at 300 rpm for 60 minutes, and obtaining the repaired water; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 50 mg / L. The results showed that after 40 minutes, the removal rate of active chromium in the water was 85.75%.
[0086] Comparative Example 6
[0087] An iron-sulfur based slurry and a preparation method thereof, comprising the following steps:
[0088] (1) Dissolve cellulose sulfonic acid, polyacrylamide, ferrous sulfate and sodium sulfide in water respectively to prepare a 2% cellulose sulfonic acid solution, a 2% polyacrylamide solution, an 8 mol / L ferrous sulfate solution and a 12 mol / L sodium sulfide solution; mix the cellulose sulfonic acid solution and the ferrous sulfate solution under normal temperature and anaerobic conditions, and stir at 400 rpm for 15 min;
[0089] (2) mixing the polyacrylamide solution with the solution obtained in step (1), and stirring at 400 rpm for 10 min;
[0090] (3) slowly adding sodium sulfide solution to the solution obtained in step (2), stirring at 400 rpm for 15 min, centrifuging the mixed solution at 5000 rpm and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension, i.e., a reducing iron-sulfur based slurry;
[0091] Wherein, the volume ratio of cellulose sulfonic acid solution: polyacrylamide solution: ferrous sulfate solution: sodium sulfide solution is 10:10:2:1.
[0092] The reducing iron-sulfur-based slurry prepared in Comparative Example 6 was applied to treat water containing heavy metal chromium, and the specific steps were as follows: adding the prepared water body heavy metal removal material to the water containing heavy metal chromium, so that the volume ratio of the two was about 150:1, stirring at a speed of 300 rpm for 60 minutes, and obtaining the repaired water body; wherein the hexavalent chromium concentration in the water containing heavy metal chromium was 40 mg / L. The results showed that after 15 minutes, the active chromium removal rate in the water was 63.55%.
Claims
1. A stabilized reducing iron-sulfur based slurry, characterized in that: The slurry is an organic matter-coagulant-ferrous sulfide nanoparticle suspension; the slurry comprises the following components in terms of mass percentage concentration: organic matter: 0.5-5%, coagulant: 1-10%, and ferrous sulfide nanoparticles: the balance.
2. The stabilized reducing iron-sulfur based slurry according to claim 1, characterized in that: The organic matter is at least one of humic acid, disodium ethylenediaminetetraacetic acid, aminotrimethylenephosphonate, ethylenediaminetetramethylenephosphonate or hydroxymethylenephosphonate; the coagulant is at least one of polyferric sulfate, polyaluminium chloride, polyacrylamide or dicyandiamide resin organic coagulant.
3. The stabilized reducing iron-sulfur based slurry according to claim 1, characterized in that: The particle size of the ferrous sulfide nanoparticles is 500-1000nm.
4. A method for preparing the stabilized reducing iron-sulfur based slurry according to claim 1, characterized in that: The following steps are involved: (1) mixing the organic matter solution with the ferrous sulfate solution and stirring to allow the ferrous ions to fully complex with the organic matter; (2) mixing the coagulant solution with the solution obtained in step (1), stirring, and encapsulating the complex of ferrous ions and organic matter therein; (3) slowly adding sodium sulfide solution to the mixed solution obtained in step (2), stirring to form nano-ferrous sulfide particles in the mixed solution, and then centrifuging and discarding the supernatant to obtain an organic matter-coagulant-ferrous sulfide nanoparticle suspension.
5. The method for preparing a stabilized reducing iron-sulfur based slurry according to claim 4, characterized in that: The ferrous sulfide content in the organic matter-coagulant-ferrous sulfide nanoparticle suspension obtained in step (3) is not higher than 80 g / L and not lower than 40 g / L.
6. The method for preparing a stabilized reducing iron-sulfur based slurry material according to claim 4, characterized in that: The volume ratio of the organic solution, coagulant, ferrous sulfate solution and sodium sulfide solution is 5:5:2:1-3:3:2:
1.
7. The method for preparing a stabilized reducing iron-sulfur based slurry material according to claim 4, characterized in that: In step (1), the mass percentage concentration of the added organic solution is 0.5-5%, and the mass percentage concentration of the added ferrous sulfate solution is 5-15 mol / L.
8. The method for preparing a stabilized reducing iron-sulfur based slurry material according to claim 4, characterized in that: In step (2), the mass percentage concentration of the coagulant solution is 1-10%.
9. The method for preparing a stabilized reducing iron-sulfur based slurry material according to claim 4, characterized in that: In step (3), the molar concentration of the added sodium sulfide solution is 5-20 mol / L.
10. Use of the stabilized reducing iron-sulfur based slurry according to claim 1 in removing heavy metals from water bodies.
Citation Information
Patent Citations
Preparation method and applications of ferrous sulfide / biological carbon composite material
CN106966456A
Magnesium based ferrous sulfide composite nanomaterial as well as preparation method and application thereof
CN108620047A
Application of cooperatively degrading trichloroethylene by means of carboxymethylcellulose-stabilized ferrous sulfide / biocharcoal composite material and microorganisms
CN108996710A
Sodium sulfide production method with iron content below 30 ppm
CN102267689A
Soil remediation agent, preparation method and applications thereof
CN110776920A